2018
DOI: 10.1038/s41419-018-0752-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-214 promotes hepatic stellate cell activation and liver fibrosis by suppressing Sufu expression

Abstract: MicroRNAs (miRNAs) have been demonstrated to modulate cellular processes in the liver. However, the role of miRNAs in liver fibrosis is poorly understood. Because the activation of hepatic stellate cells (HSCs) is a pivotal event in the initiation and progression of hepatic fibrosis, we investigate the differential expression of miRNAs in activated and quiescent rat HSCs by microarray analysis and find that miR-214 (miR-214-3p) is significantly upregulated during HSC activation. Moreover, the robust induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 35 publications
(45 reference statements)
2
53
0
Order By: Relevance
“…14 Conversely, miR-214 promotes HSC activation and liver fibrosis by suppressing Sufu expression. 15 In addition, multiple miRNAs (i.e. miR-122, miR-101, miR-133a, miR-221/222, miR-181b and miR-19b) participate in controlling HSC activation and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…14 Conversely, miR-214 promotes HSC activation and liver fibrosis by suppressing Sufu expression. 15 In addition, multiple miRNAs (i.e. miR-122, miR-101, miR-133a, miR-221/222, miR-181b and miR-19b) participate in controlling HSC activation and liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated the pivotal roles of miRNAs in the pathogenesis of liver fibrosis . A research by Ma et al reported that miR‐214 promoted the development of liver fibrosis via inducing the activation of HSCs . In addition, miR‐873‐5p has been demonstrated to be a marker for liver fibrosis and regulate the early stages of liver fibrosis .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, miRNAs were correlated with various clinical characteristics in ZZ individuals such as HSCs activation, brosis and cirrhosis, and HCC which shows the possibility of using EVs as a potential source of biomarkers for early diagnosis of disease progression. Importantly, we identi ed that of the 44 miRNAs whose levels change in the plasma EVs of AATD individuals, 5 which were higher in AATD individuals (miR-125a, miR-125b1, miR-125b2, miR-128 and miR-130b) and 1 lower (miR-6809) appear to play important roles in liver brosis (41)(42)(43)(44)(45). A large body of evidence supports the implication of the miR-125 family and miR-130b (46) in different liver diseases, including ALF (47), non-alcoholic fatty liver disease (48), cholestasis (49), and HCC (50).…”
Section: Discussionmentioning
confidence: 99%